2011
DOI: 10.1016/j.jprot.2011.07.029
|View full text |Cite
|
Sign up to set email alerts
|

2-D DIGE uterine endothelial proteomic profile for maternal chronic binge-like alcohol exposure

Abstract: Little is known about alcohol effects on the utero-placental compartment during pregnancy. For the first time, we utilized 2-D DIGE quantitative proteomics to evaluate the role of the uterus in Fetal Alcohol Spectrum Disorders (FASD) pathogenesis. Uterine artery endothelial cells were isolated from pregnant ewes, FAC sorted, validated, and maintained in culture. To mimic maternal binge drinking patterns, cells were cultured in the absence or presence of alcohol (300 mg/dl) in a compensating sealed humidified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…Antenatal ethanol exposure induces oxidative stress in various organs (Amini et al, 1996;Ramadoss and Magness, 2011;Patten et al, 2013). The fetal brain is affected by this type of stress even when the consumption of alcohol is relatively low (Chu et al, 2007;Dong et al, 2010).…”
Section: Oxidative Stress Nutritional Antioxidants and Dietary Habitsmentioning
confidence: 99%
“…Antenatal ethanol exposure induces oxidative stress in various organs (Amini et al, 1996;Ramadoss and Magness, 2011;Patten et al, 2013). The fetal brain is affected by this type of stress even when the consumption of alcohol is relatively low (Chu et al, 2007;Dong et al, 2010).…”
Section: Oxidative Stress Nutritional Antioxidants and Dietary Habitsmentioning
confidence: 99%
“…Next, we will discuss oxygen free radicals as redox balance impairment produces vasoconstriction. Substantial evidence exists to demonstrate maternal alcohol exposure increases oxidative stress markers in the fetus (11), fetoplacental compartment (40), maternal ovine uterine artery endothelial cells (69), etc., via multiple mechanisms that are discussed in other excellent review articles (9,11,27), whereas there is a paucity of human clinical studies especially in pregnant women (79). Another paracrine factor that is critical in gestational adaptations is NO.…”
Section: Effects Of Alcohol On Maternal Endocrine and Paracrine Systementioning
confidence: 99%
“…This is an important area of exploration since the vascular endothelium is programmed during pregnancy (47,48); for example, we reported that 17␤-estradiol and its metabolites induce proliferation of uterine endothelial cells only during pregnancy and not in the nonpregnant state (37). In one study, uterine artery endothelial cells were isolated from pregnant ewes, fluorescence-activated cell sorted, validated, and maintained in culture and treated with chronic in vitro binge-like alcohol (300 mg/dl, 3-h treatment on 3 consecutive days followed by 4 days without exposure for 2 wk) (69). Two-dimensional differential in gel electrophoresis separation followed matrix-assisted laser desorption time-of-flight mass spectrometry tandem mass spectrometry was then used to demonstrate that alcohol significantly decreased 30 proteins and increased 19 others in the uterine endothelium (Fig.…”
Section: Maternal Alcohol Effects On Reproductive Vasculaturementioning
confidence: 99%
See 2 more Smart Citations